PENGARUH MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Solihatun Solihatun; Akhmad Darmawan; Fatmah Bagis (Universitas Muhammadiyah Metro Lampung, 2021)
This study aims to determine the effect of motivation and work environment on job satisfaction, the influence of motivation, work environment and job satisfaction on employee performance, job satisfaction mediates the relationship between motivation on employee performance and job satisfaction mediates the relationship between work environment and employee performance. The population used is employees of the production section of PT. The Wahidatama Purbalingga Gold Herb for 200 people. The sampling technique used simple random sampling. The technique of collecting data using a questionnaire. The sample taken was 132 respondents using the Yamane formula. The data analysis used was validity test, reliability test, classic assumption test, multiple linear regression test, Adjusted R Square coefficient of determination test, f test, t test and Sobel test. Based on the results of the analysis it is proven that motivation and work environment have a significant effect on job satisfaction, motivation, work environment and job satisfaction have a significant effect on employee performance and job satisfaction mediates motivation and work environment on employee performance at PT. Wahidatama Purbalingga Gold Herb. Based on the significance value obtained, the variable that most influences employee performance is the motivation variable.Keywords: Motivation, Work Environment,Job Satisfaction, Employee Performance